Reliability Evaluation of SiC MOSFETs Under Realistic Power Cycling Tests - Farhadi M.; Vankayalapati B.T.; Akin B. (My University, 2025)
The past decade has witnessed increasing migration from silicon (Si) to silicon carbide (SiC) in power electronics applications. This is due to the unique advantages of SiC over Si counterparts, like higher breakdown field, higher band gap, and higher thermal conductivity [1], [2]. Therefore, SiC devices can operate at faster switching frequencies, higher power density, and with exceptional thermal performance. However, as this technology progressively becomes mature, questions still arise regarding its long-term reliability. These questions can be answered proactively using accelerated lifetime tests (ALTs). ALTs accelerate the aging mechanisms by amplifying the thermal and electrical stresses. The data from ALTs serve a crucial function for evaluating the sustained reliability of SiC MOSFETs through assessment of their lifespan, identification of breakdown causes, and continuous monitoring of their performance. This article introduces an ac power cycling test setup for SiC MOSFETs and discusses the correlation of aging precursors to different failure mechanisms. Also, the study identifies and presents patterns of common precursor shifts. © 2014 IEEE.